Capacity-building for Philippine Public Secondary School Teachers on Information and Communications Technology Literacy Training Program - Itaas, Estela C. (JPAIR Multidisciplinary Research, 2009)
The Bukidnon State University (BSU), a state university in the province of Bukidnon in the island of Mindanao, Philippines in partnership with the Commission on Information and Communications Technology (CICT), conducts the capacity-building for secondary school teachers in the Philippines on ICT. The training enhances teachers with the knowledge and skills in the Computer Applications and Information Management System (CAIMS). The trainers who are ICT experts facilitated the roll out of the project in the seven regions with a number of activities including hands-on and on-site training on CAIMS, installation and upgrading of computer hardware and software, data banking and continuous technical assistance. Some lessons learned include the following: a) implementation of teaching-learning strategies that integrate a range of information and communication technologies to promote and enhance students learning; b) establishment of cooperative and collaborative technology-supported and learner centered environments that engage all students in focused learning experience; c) enrichment in curriculum lessons with students effectively evaluating and using relevant and appropriate software for specific educational use.